2017
DOI: 10.1093/dote/dox009
|View full text |Cite
|
Sign up to set email alerts
|

Feeding catheter gastrostomy with the round ligament of the liver prevents mechanical bowel obstruction after esophagectomy

Abstract: Jejunostomy, which requires the fixation of the jejunum to the abdominal wall, is commonly used as an enteral feeding access after esophagectomy. However, this procedure sometimes causes severe complications, such as mechanical bowel obstruction. In 2009, we developed a modified approach to insert an enteral feeding tube through the reconstructed gastric tube using the round ligament of the liver. The aim of this study is to investigate the usefulness of this approach as compared to the approach through jejuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…In the previous report, laparoscopic procedure and fixation of the jejunum only at the catheter insertion point resulted in 11.5% of BOFJ [17]. On the other hand, open abdominal surgery and longitudinal fixation of the catheter resulted in less than 6.0% of BOFJ [1820]. Judging from these, the reason of our high incidence of BOFJ might be fewer abdominal adhesion condition with laparoscopy and small area fixation suture around the catheter via a small abdominal incision, resulted in shorter distance between the catheter and midline, creating a large internal hernia space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous report, laparoscopic procedure and fixation of the jejunum only at the catheter insertion point resulted in 11.5% of BOFJ [17]. On the other hand, open abdominal surgery and longitudinal fixation of the catheter resulted in less than 6.0% of BOFJ [1820]. Judging from these, the reason of our high incidence of BOFJ might be fewer abdominal adhesion condition with laparoscopy and small area fixation suture around the catheter via a small abdominal incision, resulted in shorter distance between the catheter and midline, creating a large internal hernia space.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits of a feeding jejunostomy after esophagectomy, an alternative enteral feeding method would be desirable to avoid BOFJ. Some researchers have recommended insertion of the feeding catheter into the gastric tube [20, 22] or duodenum [23], through the round ligament of liver, rather than through the jejunum. However, insertion of a feeding catheter into the gastric tube requires a retro-sternum reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some researchers have recommended insertion of the feeding catheter into the duodenum [ 18 ] or gastric tube [ 20 , 22 ], through the round ligament of the liver, rather than through the jejunum to prevent BOFJ.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with posterior mediastinal route reconstruction, constructing a feeding gastrostomy with round ligament is sometimes difficult because the location of gastric antrum is separate from the round ligament [ 22 ]. Another concern about duodenostomy has been inflammation around the duodenal bulb or pylorus following leakage and/or catheter-related abscess, leading to gastric tube stasis due to edema of the duodenum and/or pylorus [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is considered to cause twisting and kinking. Several authors reported that jejunal attachment to the parietal peritoneum may cause mechanical bowel obstruction at the catheter insertion site (7,8). As a new method to reduce complications, Oya et al and Kawai et al…”
Section: Discussionmentioning
confidence: 99%